Pengawasan Pengelolaan Dana Pensiun di Indonesia: Analisis Terhadap Praktik Fraud dan Efektivitas Regulasi - Arthur Arthur; Hasim Sukamto; Diana Ria Winanti Napitupulu (Jurnal Syntax Admiration, 2024)
Pension funds are one of the important instruments in providing old-age security for workers. However, in practice, there are several cases where pension fund managers are involved in fraud that harms pension participants. This research aims to examine the supervision carried out on pension funds, especially in the context of overcoming fraud practices by pension fund managers in Indonesia. Using a normative and empirical juridical approach, this research examines the effectiveness of existing regulations and the application of sanctions against violations that occur. Based on the analysis, it is found that despite the existence of fairly strict regulations, fraudulent practices in pension fund management still occur due to weak supervision and law enforcement. The case study raised in this research shows that the involvement of supervisory institutions such as the Financial Services Authority (OJK) and related legal entities needs to be increased so that pension fund management runs more transparently and accountably.